2015
DOI: 10.1016/j.surfcoat.2014.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion behavior of TiBxCy/a-C nanocomposite coating in strong oxidant disinfectant solutions

Abstract: Corrosion and tribocorrosion studies of a TiB x C y /a-C coating deposited on AISI 316L steel have been performed in an aqueous solution of 0.26 vol.% acetic, 0.16 vol.% peracetic and 0.18 vol.% hydrogen peroxide (commercial product Oxonia 1 vol.%). The corrosion current density of the TiB x C y /a-C coating ranges on the same order as bare steel but with a significantly decreasing friction (0.1 vs. 0.6) and wear rate (~10 times lower). The compact microstructure of the coating hinders the access of the aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Several investigations have therefore been made by connecting the working electrode to a platinum microelectrode through the ZRA [28,[91][92][93]. Quan et al (2006) [94] evaluated the corrosion-wear of TiN coated AISI 316 stainless steel in sulphuric acid solution and found that the corrosionwear mechanism of the coatings depended on their substrate properties.…”
Section: Tribocorrosion Assessment By Electrochemical Noisementioning
confidence: 99%
“…Several investigations have therefore been made by connecting the working electrode to a platinum microelectrode through the ZRA [28,[91][92][93]. Quan et al (2006) [94] evaluated the corrosion-wear of TiN coated AISI 316 stainless steel in sulphuric acid solution and found that the corrosionwear mechanism of the coatings depended on their substrate properties.…”
Section: Tribocorrosion Assessment By Electrochemical Noisementioning
confidence: 99%
“…It was reported by Oliveira that the corrosion resistance could be enhanced up to 59 times compared to the bare SS304 substrate with controlled hydrogen and carbon contents [41]. E. Gracia-Escosa studied TiB x C y /a-C coatings deposited on AISI 316L steel in an aqueous solution of 0.26 vol.% acetic acid, 0.16 vol.% peracetic acid and 0.18 vol.% hydrogen peroxide [42]. The corrosion current density of the TiB x C y /a-C coating is in the same range as bare steel but with a significantly decreased coefficient of friction (0.1 vs. 0.6) and wear rate (~10 times lower).…”
Section: Vapor Depositionmentioning
confidence: 99%
“…The results indicated no influence of the tool steels on the tribological behavior and increasing wear with increasing temperatures. Gracia-Escosa et al [9] investigated the tribological behavior of two different tool steels with pinon-disc tests and found similar wear behavior. However, the so far published studies did not show how the frictional behavior can be specifically influenced by choosing the right tool material or surface properties.…”
Section: Introductionmentioning
confidence: 99%